2015
DOI: 10.1097/fch.0000000000000066
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Low-Income African American Women's Expectations, Preferences, and Priorities in Prenatal Care

Abstract: We aimed to explore factors affecting prenatal care attendance and preferences for prenatal care experiences among low-income black women by conducting a focus group study using a community-based participatory research framework and nominal group technique. Discussions were audiorecorded, transcribed, and coded by trained reviewers. Friends/family and baby's health were the top attendance motivators. Greatest barriers were insurance, transportation, and ambivalence. Facilitators included transportation service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
97
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(100 citation statements)
references
References 23 publications
2
97
0
1
Order By: Relevance
“…This is consistent with previous research demonstrating higher levels of care satisfaction among women randomized to group versus individual usual care (Ickovics et al 2007) and may be the result of reduced wait times for group care visits, as well as increased social support, education, and continuity of care and personal connection with healthcare providers women value in prenatal care services (Edmonds et al 2015; Novick et al 2011). Although the number of women eligible to attend varied, average attendance rates remained consistent across sessions, indicating that once women decide to attend group sessions, they are likely to keep coming until childbirth or all sessions for their group sessions have been completed.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous research demonstrating higher levels of care satisfaction among women randomized to group versus individual usual care (Ickovics et al 2007) and may be the result of reduced wait times for group care visits, as well as increased social support, education, and continuity of care and personal connection with healthcare providers women value in prenatal care services (Edmonds et al 2015; Novick et al 2011). Although the number of women eligible to attend varied, average attendance rates remained consistent across sessions, indicating that once women decide to attend group sessions, they are likely to keep coming until childbirth or all sessions for their group sessions have been completed.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the work of Tucker Edmonds et al, 2015, our findings show that there are health systems factors that negatively affect women of color's healthcare experiences. Specifically, the lack of connection participants felt to their providers, the role of trainees in their care provision and the participants' perceptions of a lack of caring or respect from their providers of care were also identified in our findings.…”
Section: Discussionsupporting
confidence: 74%
“…It is hypothesized that women of color experience longer lifetime exposure to chronic stress, which may lead to fluctuations in allostatic load (wear and tear) and contribute to the higher risk of PTB for these women (Braveman et al, 2015;Giurgescu et al, 2011). Other investigators have suggested that women of color experience discrimination, racism and disrespect in healthcare encounters and that this affects the health of women and their infants (Rankin et al, 2011;Tucker Edmonds et al, 2015;Ertel et al, 2012;Pullen et al, 2014;Nuru-Jeter et al, 2009;Dominguez et al, 2008;Slaughter-Acey et al, 2016). A recent study (SlaughterAcey et al, 2016) found significant associations between racial mircoaggressions and PTB in women who had mild to moderate, but not severe, depressive symptoms, but did not find a significant association between PTB and overall perceived stress.…”
Section: Background and Significancementioning
confidence: 99%
“…Our findings are not generalizable beyond a demographically similar populationd–by design exclusively low income, to focus on a population at known risk for disproportionately poor outcomes. It has been well-established that disparities in both accessibility and acceptability of prenatal care independently affect African American or Black women when compared with other low-income women in the United States (Bryant et al, 2010; Tucker Edmonds et al, 2015). Aspects of care such as health system trust and perceived racism, in addition to social determinants of health and differences in health status, have been implicated in these disparities (Attanasio & Kozhimannil, 2015; Gadson, Akpovi, & Mehta, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Cost, transportation, perception of low value of prenatal care by patients, and poor institutional practices have been identified as key barriers to prenatal care utilization (Mazul, Salm Ward, & Ngui, 2016; Tucker Edmonds, Mogul, & Shea, 2015). Tailoring prenatal care models to those who face disproportionate barriers and risk has been suggested as a way to adjust “undifferentiated” prenatal care delivery to further impact perinatal outcomes such as birth-weight and preterm delivery rate (Krans & Davis, 2012).…”
mentioning
confidence: 99%